Factors related to complications from general anesthesia in patients with obstetrics and gynecology operation in Sichon Hospital, Nakhon Si Thammarat Province - Sutin, Pratthana (Health Science Journal of Nakhon Ratchasima College, 2024)
This study was a cross-sectional descriptive study. The aim was to study the incidence and correlation of complications in obstetrics and gynecology patients with general anesthesia undergoing open abdominal surgery. Sample group consisted of 75 gynecological patients undergoing abdominal surgery and receiving general anesthesia at Sichon hospital. Data were collected by questionnaires and analyzed using descriptive statistics; correlation was analyzed by using Chi square test and Fisher’s exact test. Results showed that 38.00% of the samples were under 30 years old, 80.00% had underlying diseases and 66.70% underwent cesarean section. Moreover, 88.00% of patients were classified as Class II under American association of Anesthesiologist (ASA) criteria, anesthesia duration less than 60 minutes was 69.34% and duration in operating room less than 60 minutes was 61.30%. The incidence of complication was 29.33 per 100 people. The most of complications founded were 21.30% of vomiting and nausea, and 8.00% of hypothermia. Factors related to postoperative complications of general anesthesia in obstetrics and gynecology patients at statistical significance (p-value< 0.05 level) included ASA class and duration of anesthesia.